Association Between Impairment of DNA Double Strand Break Repair and Decreased Ovarian Reserve in Patients With Endometriosis - Choi, Young Sik; Park, Ji Hyun; Lee, Jae Hoon; Yoon, Jeong-Kee; Yun, Bo Hyon; Park, Joo Hyun; Seo, Seok Kyo; Sung, Hak-Joon; Kim, Hyun-Soo; Cho, SiHyun; Lee, Byung Seok (Frontiers in Endocrinology, 2018)
Background: Repair of DNA double strand break (DSB) is an important mechanism for maintaining genetic stability during a DNA damage event. Although, a growing body of recent evidence suggests that DNA DSBs and related repair mechanisms may be important in ovarian aging and in various cancers, there are few reports in endometriosis. We, therefore, examined expression levels of genes pertaining to DNA DSB repair in patients with endometriosis to assess the potential effects on ovarian reserves. Materials and methods: A total of 69 women undergoing laparoscopic surgery for endometriosis and other benign conditions was included; endometriosis group (n=38) vs. controls (n=31). DNA DSBs in endometrial and ovarian tissues of both groups were compared via immunohistochemistry, aimed at γ-H2AX expression. To gauge genotoxin-induced DNA DSBs in endometrial stromal cells, γ-H2AX expression was determined by western blot after H2O2 treatment of cultured endometrial stromal cells (endometriosis group and controls) and Ishikawa cell-line cultures. Endometrial and ovarian tissue levels of BRCA1, BRCA2, Rad51, and ATM (ataxia-telangiectasia mutated) mRNA expression were also compared. Correlations between expression levels of genes of interest and serum anti-müllerian hormone (AMH) levels were assessed as well. Results: Expression of γ-H2AX in immunostained endometrial and ovarian tissue preparations was greater in the endometriosis group, compared with controls. After H2O2 treatment, γ-H2AX expression levels were also significantly greater in cultured stromal cells of the endometriosis group and in the Ishikawa cell line than in controls. Endometrial expression of BRCA1 and Rad51 mRNA proved significantly lower in the endometriosis group (vs controls), as did ovarian expression of BRCA1 and BRCA2 mRNA. Serum AMH concentration showed a significant correlation with ovarian BRCA1 mRNA expression in women with endometriosis (p=0.03). Conclusions: In women with endometriosis, expression levels of various genes implicated in DSB repair are decreased and ovarian BRCA1 expression correlates with ovarian reserves. These findings indicate that impaired DSB repair may contribute to diminished ovarian reserves in this setting.